HOW TO USE ONLINE MATERIALS IN THE VIRTUAL CLASSROOM - Diyorova Mahliyo (Scholars Digest Publishing, 2023)
Using realia in offline lessons is better than using it online, especially for people who learn better by touching things. Because they can touch and feel them with their hands. It means that offline teaching with realia is useful and works well.
Keywords: clip, skill, participants, design, websites, blogs, skim, authentic